Produção de biossurfactantes bacterianos em solos utilizando bioaumentação e bioestimulação - Machado, Thaís Strieder (2018)
Despite the constant progress in understanding the mechanisms related to the effects of biosurfactants in bioremediation processes of oily residues, there is a gap in the literature regarding the measurement of the in situ production of these compounds. It is known the positive influence of biosurfactants, but there are also cases in which no effects or negative effects were observed. Therefore, it is necessary to expand the studies in contaminated sites with respect to the autochthonous microbial behavior when performing the bioaugmentation and biostimulation for the production of biosurfactants, as well as the measurement of this production in the soil, and its performance in the biodegradation of the contaminant. This study aimed to stimulate and measure the production of biosurfactants in situ during the bioremediation of diesel oil in clay soil through bioaugmentation and biostimulation. Initially, surfactin was produced by submerged fermentation using the bacterium Bacillus methylotrophicus and whey as a culture medium to standardize methodologies for measuring biosurfactants in aqueous medium. The biosurfactant produced was added to soil and performed studies to standardize the soil biocomposite extraction methodology and its measurement. In a second stage, it was studied the influence of the addition of partially purified surfactina of the fermentation media, on the growth of microorganisms in tubes and on the CO2 release of the autochthonous microorganisms of the soil. In the third phase of the study, bioremediation of soil contaminated with 20% of diesel oil was carried out, using as strategies to stimulate the in situ production of biosurfactants, bioaugmentation and biostimulation. The bioremediation was performed for 60 days and the responses of the contaminant removal rate, the evaluation of the degradation and the production of in situ biosurfactants through infrared spectra were evaluated, further the measurement of the biosurfactants in situ as a function of the reduction of the surface tension. Biosurfactants were produced in the amount of interest, used for the elaboration of the standard curves by surface tension and Biureto method to evaluate the production of biosurfactants in situ. It was possible to perform the Biureto’s standard curve for the determination of surfactin, however, when this was added to the soil and the extraction was performed, the method did not show sensitivity for the recovery of the biocomposite in the soil, since the analysis was interfered with by other compounds extracted from the soil. The biosurfactant did not present an antimicrobial effect when used in the tests to determine the minimum inhibitory concentration and in the evaluation of the release of CO2 in soil. In the influence test of the addition of surfactin to soil, it was verified that besides this one did not present antimicrobial action, it acted as a biostimulant in the soil, increasing the CO2 release from 9.78 to 216.29 mg CCO2/kg of soil in addition of 4000 mg/kg surfactin after 35 days of experiment. In the bioremediation test of diesel oil, biostimulated treatment presented 60.48% of biodegradation at the end of 60 days of experiment. However, the treatments with bioaugmentation and biostimulation did not present a significant reduction of the contaminant when compared to natural attenuation. It was not possible to evaluate the biodegradation of diesel oil and the in situ production of biosurfactants through infrared spectra. By this mean, the in situ stimulation of the surfactin production from the relations used in the submerged fermentation is not appropriate for a concentration of 20% of diesel oil in clay soil, since a high contaminant rate was adsorbed to the soil, overestimating the effect of biodegradation.